Influence of Perioperative Dexamethasone on the Delayed Union in Mandibular Fractures - Sheikh, Zulakha Akhtar; Alam, Jehan; Shah, Ruqaya; Samreena; Naseem, Sobia; Ahmed, Javeria (Indus Journal of Bioscience Research, 2025)
Background: Mandibular fractures are considered to be one of the most frequent facial bone fractures which occur due to trauma that causes functional, as well as aesthetic, impairment. Perioperative use of dexamethasone is associated with postoperative inflammation and pain control due to its effects as a potent glucocorticosteroid. However, dexamethasone has been reported to have an impact on bone healing, thus posing a threat when used in treatment regimens because it is likely to slow the fracture union rate. Objective: The purpose of this case control study is to determine the effect of perioperative dexamethasone in causing delayed union in patients treated by surgical management of mandibular fractures. Study design and setting: A prospective cohort study was conducted at the Department of Oral & Maxillofacial Surgery, Jinnah Postgraduate Medical Centre, Karachi from March 2024 to September 2024. Methodology: The study was conducted on 75 patients who were divided into two groups: One of the two groups that were enrolled in this study, one group of patients receiving perioperative dexamethasone and the other group acting as the control group. Clinical and radiographic examinations were done in different days or weeks after surgery to evaluate the healing status. Results: The results obtained showed that there was a higher incidence of delayed fracture union in the dexamethasone group (26.3%) than in the control group (10.8%) with longer mean healing time in the dexamethasone group. Conclusion: These results indicated that although dexamethasone can help minimize postoperative inflammation for a limited amount of time, it will have prejudicial effects on bone healing for a considerably long term period especially for the patients in the high-risk category. Additional studies must be conducted to determine how dexamethasone affects bone repair and to establish proper therapeutic strategies.